Atividade ovicida de fungos isolados do solo no sul do Brasil sobre ovos de Toxocara canis - Maia Filho, Fernando de Souza (2012)
The high prevalence of Toxocara canis in dogs, associated with environmental contamination and the resistance of eggs in the soil increase the exposure of humans front of the parasite. Moreover, the difficulties of implementation of control measures and disinfection, allied to the problems inherent to chemical control, justifying the need for alternative measures that assist in controlling parasitoses transmitted by the soil. Among these measures, we highlight the use of nematophagous fungi.This study had the objective of valuating the activity of in vitro ovicide of isolated fungi based on soil collected in public places in the city of Pelotas, RS, Brazil. Samples of soil from ten localities were sowed in agar water 2% with antibiotics and incubated at 25ºC for 21 days. The ovicide activity of the fungal isolates obtained was tested in vitro in five repetitions for each analyzed insulator. An mL of an embryonated egg suspension of Toxocara canis (103 eggs) was poured over the fungal cultures grown in agar water for 10 days. At intervals of 7, 14 and 21 days, 100 eggs were removed from each plaque and evaluated in optical microscopy. Acremonium spp., Aspergillus spp., Bipolaris spp., Fusarium spp., Gliocladium spp., Mucor spp. and Trichoderma spp. were isolated from the soil. In this order, a significant ovicidal type 3 effect was observed in Trichoderma spp., Fusarium complex solani and Acremonium spp.. Trichoderma spp. presented an ovicidal effect on the 14th day of fungus-egg interaction. The other fungal genera tested presented a type 2 effect. The results obtained showed the presence of nematophagous fungi parasites of eggs in soil in the Southern region of Brazil and demonstrated the ovicidal activity of Trichoderma spp. and Fusarium complex solani on T. canis eggs.